Crafting a public for geoengineering. (May 2017) - Bellamy, Rob; Lezaun, Javier
In a short period of time, climate 'geoengineering' has been added to the list of technoscientific issues subject to deliberative public engagement. Here, we analyse this rapid trajectory of publicization and explore the particular manner in which the possibility of intentionally altering the Earth's climate system to curb global warming has been incorporated into the field of 'public engagement with science'. We describe the initial framing of geoengineering as a singular object of debate and subsequent attempts to 'unframe' the issue by placing it within broader discursive fields. The tension implicit in these processes of structured debate – how to turn geoengineering into a workable object of deliberation without implying a commitment to its reality as a policy option – raises significant questions about the role of 'public engagement with science' scholars and methods in facilitating public debate on speculative technological futures.